2004
DOI: 10.1136/emj.2003.004853
|View full text |Cite
|
Sign up to set email alerts
|

Preconsultation use of analgesics on adults presenting to the emergency department with acute appendicitis

Abstract: Objective: 279 cases of appendicitis were reviewed and compared for the difference between those patients who received pain medication before consulting a surgeon and those who were not treated with analgesics. Methods: All patients aged 15 years and older who underwent appendicectomy for appendicitis between 1 July 2001 and 30 June 2002 were divided into group 1 (those who received preconsultaion use of analgesics) and group 2 (those who were not treated with analgesics). The following measures were compared:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 9 publications
(6 reference statements)
0
2
0
Order By: Relevance
“…Two retrospective analyses of patients with proven appendicitis did not find any difference in the rate of perforated appendicitis between patients who received or did not receive analgesia. 13,43 Reports of analgesia administration leading to adverse consequences remain limited to case reports. 15 While giving opiates to patients with acute abdominal pain appears to alter the physical examination, the use of opiates leads to virtually no increase in incorrect management decisions.…”
Section: Scenario Resolutionmentioning
confidence: 99%
“…Two retrospective analyses of patients with proven appendicitis did not find any difference in the rate of perforated appendicitis between patients who received or did not receive analgesia. 13,43 Reports of analgesia administration leading to adverse consequences remain limited to case reports. 15 While giving opiates to patients with acute abdominal pain appears to alter the physical examination, the use of opiates leads to virtually no increase in incorrect management decisions.…”
Section: Scenario Resolutionmentioning
confidence: 99%
“…Chong et al 20 reviewed the hospital charts of 297 patients with appendicitis and found that the use of parenteral analgesics before the consultation did not cause a significant delay to surgery and was not associated with an increased rate of serious complications such as perforated appendicitis 20. Vermeulen et al reported improvement in pain severity without changing the appropriateness of the surgeon’s decision-making 21.…”
Section: Discussionmentioning
confidence: 99%